Caring for children with physical disability in Kenya: potential links between caregiving and carers' physical health. - Geere, J; Gona, J; Omondi, F; Kifalu, M; Newton, C; Hartley, S (2013)
BACKGROUND: The health of a carer is a key factor which can affect the well-being of the child with disabilities for whom they care. In low-income countries, many carers of children with disabilities contend with poverty, limited public services and lack assistive devices. In these situations caregiving may require more physical work than in high-income countries and so carry greater risk of physical injury or health problems. There is some evidence that poverty and limited access to health care and equipment may affect the physical health of those who care for children with disabilities. This study seeks to understand this relationship more clearly. METHODS: A mixed methods study design was used to identify the potential physical health effects of caring for a child with moderate-severe motor impairments in Kilifi, Kenya. Qualitative data from in-depth interviews were thematically analysed and triangulated with data collected during structured physiotherapy assessment. RESULTS: Carers commonly reported chronic spinal pain of moderate to severe intensity, which affected essential activities. However, carers differed in how they perceived their physical health to be affected by caregiving, also reporting positive benefits or denying detrimental effects. Carers focussed on support in two key areas; the provision of simple equipment and support for their children to physically access and attend school. CONCLUSIONS: Carers of children with moderate-severe motor impairments live with their own physical health challenges. While routine assessments lead to diagnosis of simple musculoskeletal pain syndromes, the overall health status and situation of carers may be more complex. As a consequence, the role of rehabilitation therapists may need to be expanded to effectively evaluate and support carers' health needs. The provision of equipment to improve their child's mobility, respite care or transport to enable school attendance is likely to be helpful to carers and children alike.